Penerapan Metode Simple Additive Weighting Pada Penentuan Tingkat Kesejahteraan Penduduk Provinsi Nusa Tenggara Timur - Kaho, Monica Louisa Ratu; Tanaamah, Andeka Rocky; Wowor, Alz Danny (Proceedings of KNASTIK, 2013)
The importance of a system not only helping the work done quickly and easy but also could result accurate information. Recently many government's program especially related with society walfare those are not touch the right target because the inaccurate information about society welfare. Answering this problem, we need a system that resulting the accurate information about people welfare. To determine the level of people walfare use many criteria and alternative, to easing the determination of welfare level we need to applying Simple Additive Weighting method on the system because Simple Additive Weighting is one of completion method that involve many criteria and alternative. Through the information that result by the system that is level of people welfare in each regency of East Nusa Tenggara, hopefully could help the authority to determine which region to be priority for the implementation of the welfare developing program.